Chinese International Commercial Courts: Overview and Potential Questions Around It - Asal Juraeva; Khumoyun Soyipov (Faculty of Law, Hasanuddin University, 2022)
People’s Republic of China (PRC) established China’s International Commercial Courts (CICC) and became one of the global competitors that offers international commercial dispute settlement service. Basically, the CICC formed to assist the enhancement of the “Belt and Road Initiative”. The formation of the CICC was an important progress in the judicial system of the PRC. The Supreme People’s Court (SPC) of the PRC equips the CICC with the necessary judicial interpretation. This article analyses the establishment of the CICC and its significant features. The goal of this research is to illustrate a detailed overview and thorough research regarding to the CICC. The current work also provides answers to the potential misunderstandings around the CICC. Based on the existing works of distinguished scholars some improvements regarding to CICC is incorporated in the research. The author also provides a comprehensive analysis of the functioning and structure of the CICC.